Hot-water dipping effect on postharvest quality and metabolite profiling of Bentong ginger (Zingiber officinale roscoe) stored at low temperature - Abdul Shukor, Nur Indah (2021)
Ginger is a tropical produce that is susceptible to chilling injury (CI). Storing ginger below 15 °C will defect its postharvest quality as it is susceptible to chilling injury (CI). Therefore, the objective of this experiment was to evaluate the effects of storage temperatures and storage durations on the physico-chemical qualities of rhizomes. The collected rhizomes from Bentong were stored at 5, 15, and 25 C and were kept for 0, 8, 16, and 24 days. The experiment was laid out as a randomized complete block design (RCBD) and analysed as a two-way factorial with four replications. For physical attribute, storage under 15 C showed that weight loss was concomitant with the firmness of rhizomes and was supported by a positive correlation between weight loss and firmness. For colours, changes of the values of h were gradual when the rhizomes were stored at 15 C contrary to chilling of rhizomes at 5 C suggesting that the colour of the rhizomes was managed to be maintained at such condition. The phytochemical analysis resulted in a similar increment in total phenolic and flavonoid when stored at 5 and 15 C up to 16 d of storage durations. It also showed that storage at 25 C could retain 6-gingerol and 6-shogaol up to 16 d of storage. For DPPH activities, the antioxidant capacity became weaker, especially during storage at 25 C as compared to 5 C of storage. Hot water treatment is developed for disease control and provides an alternative to the application of synthetic chemicals. In conjunction to mitigate CI symptoms, a study on hot water dip at 45 C for 0, 5, 10, and 15 min and immediately stored at 5 C for 0, 8 and 16 d were assessed. Storage at 5 °C was chosen as it represents chilling temperature. The postharvest qualities were expected to be prolonged under chilling temperature after being treated in hot water treatment. The experiments were conducted using RCBD, analysed as a two-way factorial with four replications and evaluated for physico-chemical qualities. From the results, the rhizome weight loss, increased proportionally with dipping durations and storage durations. For firmness, dipped rhizome for 5 min at 45 C was found to maintain the rhizome firmness along storage as compared to other dipping durations. The hue (hº) colour value of undipped rhizome resulted in a significant decline after 16 d of storage. Exposed rhizome for 5, 10 and 15 min seemed to maintain the hº of the rhizome after storage at 5 C. The lightness of colour (L*) also responded similarly. The decrease in hº from yellow to slightly brown also indicated rhizome browning. This was supported by a sharp increase of browning index in undipped rhizome within 16 d of storage at 5 C. Rhizome held at 45 C / 5 min managed to reduce browning as compared to other durations. Dipping for 15 min resulted in a significant increase in TPC, TFC and 6-gingerols, especially at 16 days of storage durations whilst DPPH activity was achieved when dipped for 5 min. Metabolomic profiling on hot water dipped rhizomes has identified two secondary metabolites groups: gingerols-related compounds and diarylheptanoid group. The distinct separation between hot water dip treatment at 5, 10, and 15 min and control were observed via OPLS-DA. The heat map showed the distribution of the up and down regulation of the identified metabolites. Based on the distribution, heat map assists in suggesting the optimum durations of hot water treatment at 45 C for 5 min to be the optimum duration in reducing browning index that could be an indicator for chilling injury. In conclusion, preconditioning of ginger rhizomes by hot water treatment at 45 °C increased chilling tolerance upon storage at chilling temperature.